(untitled) (Polis (Santiago), 2018)
Faced with the traditional or positivist science that stands outside history, culture and language, the author presents the thinking of Sarkar, who does not argue for an anti-science, anti-technology or falls into a science that would exist outside the social and political, but one within context, arguing for a new science of society. This paper raises important questions, such as: in what direction will then move social sciences: towards empathy and interpretation or towards disinterest and distance? Are we close to losing the universal perspectives as power and knowledge are localized and relativized? Or we are dealing with a new model of the real close, that becoming dominant will reformulate the categories of "science", "local" and "universal"?